The contribution of conveyed coal to mine heat problems - Watson, Andrew Gordon (1981)
As coal mines get deeper, more mechanised and more productive the heat load on the ventilation system increases. In certain cases to the point where serious environmental problems may arise. To continue mining in these demanding conditions the sources of heat must be identified and evaluated so ameliorative measures may be taken. Due to the trend towards mining at greater rates and further from the shaft, mined coal on the conveyors is being recognised as a heat source of growing importance. This thesis describes its investigation.